GLACIOLOGICAL CHARACTERISTICS OF AN ANTARCTIC INLAND PLATEAU - アゲタ, ユタカ; オクヒラ, フミオ; カミヤマ, コキチ; キクチ, トキオ; AGETA, Yutaka; OKUHIRA, Fumio; KAMIYAMA, Kokichi; KIKUCHI, Tokio (National Institute of Polar Research, 1987)
P(論文) Glaciological observations on the high plateau were made along a route of the oversnow traverse by the 26th Japanese Antarctic Research Expedition in 1985. The shape of the domelike plateau (Valkyrjedomen), which is the second highest in Antarctica, and the position of ice divides have been known more than before. The highest place of this dome was found at 77°22′S, 39°37′E with an altitude of 3807m by the use of Navy Navigation Statellite System. The surface slope, net accumulation, configuration of snow surface, ram hardness, 10m snow temperature and others were observed. From these results, the characteristics of katabatic winds region were not found in the region higher than the altitude around 3400-3600m, which was about 400m higher than such altitude in the case of Mizuho Plateau. Surface slopes change to less than 2×(10)^<-3> in the higher area from such altitudinal boundaries in both cases of the present study and Mizuho Plateau. From the observation of surface configuration, it was known that the directions of prevailing winds changed from southeast in the katabatic winds region to northeast around the highest place of the dome. On the basis of these results, patterns of atmospheric circulation over the plateau and its relation with the glaciological aspects are briefly discussed. departmental bulletin paper